1999
DOI: 10.1073/pnas.96.20.11589
|View full text |Cite
|
Sign up to set email alerts
|

Slow transport of unpolymerized tubulin and polymerized neurofilament in the squid giant axon

Abstract: A major issue in the slow transport of cytoskeletal proteins is the form in which they are transported. We have investigated the possibility that unpolymerized as well as polymerized cytoskeletal proteins can be actively transported in axons. We report the active transport of highly diffusible tubulin oligomers, as well as transport of the less diffusible neurofilament polymers. After injection into the squid giant axon, tubulin was transported in an anterograde direction at an average rate of 2.3 mm͞day, wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
72
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(74 citation statements)
references
References 39 publications
2
72
0
Order By: Relevance
“…Specifically, the velocities reported in vitro have slightly lower mean anterograde (0.38 m/s vs. 0.27 m/s) and retrograde (0.49 m/s vs. 0.29 m/s) velocities than those described by Wang et al (2000). Further evidence that fully polymerized NFs are substrates of in situ active transport is provided by studies in squid giant axons in which injected fluorescent mammalian NFs were transported as large nonmonomeric complexes (Galbraith et al, 1999). However, the hypothesis raised by the present analysis that the in vitro bidirectional motion of fully polymerized mature NF polymers along MTs may reflect the slow transport of NFs in vivo does not exclude the existence of other transport mechanisms of NF subunits in living cells.…”
Section: Transport Of Nfs In Partially Filamentous Formmentioning
confidence: 71%
See 1 more Smart Citation
“…Specifically, the velocities reported in vitro have slightly lower mean anterograde (0.38 m/s vs. 0.27 m/s) and retrograde (0.49 m/s vs. 0.29 m/s) velocities than those described by Wang et al (2000). Further evidence that fully polymerized NFs are substrates of in situ active transport is provided by studies in squid giant axons in which injected fluorescent mammalian NFs were transported as large nonmonomeric complexes (Galbraith et al, 1999). However, the hypothesis raised by the present analysis that the in vitro bidirectional motion of fully polymerized mature NF polymers along MTs may reflect the slow transport of NFs in vivo does not exclude the existence of other transport mechanisms of NF subunits in living cells.…”
Section: Transport Of Nfs In Partially Filamentous Formmentioning
confidence: 71%
“…As described by many groups, NFs can be transported as filaments (Galbraith et al, 1999;Yabe et al, 1999;Wang et al, 2000) and we have shown here in vitro transport of filamentous NFs along MTs. Jung and Shea (1999) reported that NFs transported down the optic nerve are phosphorylated and antibodies to the phosphorylated form of NF-H and NF-M specifically disrupt NF translocation.…”
Section: A Reconstituted System For Slow Axonal Nf Transport?mentioning
confidence: 76%
“…In contrast, studies on cultured rat sympathetic and cortical neurons by ourselves and others have reported that GFP-tagged neurofilament proteins move in a predominantly filamentous form (Roy et al, 2000;Wang et al, 2000;Wang and Brown, 2001;Ackerley et al, 2003;Uchida and Brown, 2004). In squid, one study has described the movement of fluorescently labeled neurofilament protein in giant axons and concluded that neurofilament protein is transported as assembled polymers (Galbraith et al, 1999), whereas another study has described the movement of punctate structures containing neurofilament protein in extruded axoplasm and concluded that neurofilament protein is transported in an unassembled form (Prahlad et al, 2000).…”
Section: Introductionmentioning
confidence: 89%
“…Originally, it was believed that neurofilaments were transported as part of the slow transport system, along with tubulin and actin. However, recent studies of green fluorescent protein (GFP)-labeled neurofilaments transfected into neurons or injected into axoplasm have shown that axonal transport of neurofilaments is more complex than previously assumed (Galbraith et al, 1999;Prahlad et al, 2000;Wang et al, 2000;Yabe et al, 2001a,b). Apparently, both NF-M and NF-H move at fast rates followed by very long pauses, or by "fits and starts," giving the impression that most neurofilaments are stationary but a few move rapidly in bursts, in both directions.…”
Section: A Model Of Topographic Regulation Of Nf Protein Phosphorylatmentioning
confidence: 95%
“…As polymeric NFs are slowly transported within the axon, proline-directed kinases sequentially phosphorylate tail domain KSP repeat sites; this promotes further extension of sidearms and crossbridge formation between NFs and microtubules, which assemble into a stable cytoskeletal core. Inasmuch as the giant axons grow continuously throughout the one-year life of the squid, axon growth is dynamic, with a crossbridged cytoskeletal core moving slowly, if at all, surrounded by more soluble tubulins and smaller moving NF polymers that become integrated into the expanding cytoskeleton (Galbraith et al, 1999). Sustaining this dynamic process of assembly and transport is a more robust phosphorylation complex of active kinases and phosphatases to ensure continuous growth in length and diameter of the underlying cytoskeletal network.…”
Section: A Model Of Topographic Regulation Of Nf Protein Phosphorylatmentioning
confidence: 99%